AN ANALYSIS OF THE VALIDITY AND RELIABILITY OF ENGLISH EXAMINATIONS: A STUDY AT A SENIOR HIGH SCHOOL IN KEFAMENANU - Arcelibur, Dionesia Nurani; Semiun, Thresia Trivict; Sahan, Anselmus (MEDIA DIDAKTIKA, 2025)
This study analyzed the validity and reliability of the English language school exam at a senior high school in Kefamenanu during the 2023/2024 academic year. A mixed-method approach was employed, with content validity assessed by matching test items to the blueprint and reliability measured using the Kuder-Richardson 20 (KR-20) formula. The results indicated that the test had a validity rate of 55%, which was classified as moderate due to some items not aligning with the specified indicators. Meanwhile, the reliability coefficient was 0.89, demonstrating a very high correlation and strong consistency of test results. It is recommended that the school improve the exam blueprint and ensure that all test items accurately reflect the taught material.